Areal features of the anglophone world - Hickey, Raymond (Topics in English linguistics, 2012)
The present volume seeks to unite the research of a range of scholars working on features of non-standard, vernacular English which show an areal distribution, i.e. which cluster geographically across the world. The volume is concerned with dialect input, innovations among varieties of English andthe areal diffusion of features among varieties. These and similar issues form the central focus of the volume.